Pengaruh Profitabilitas, Ukuran Perusahaan, dan Leverage Terhadap Manajemen Laba (Studi Empiris pada Perusahaan di Sub Sektor Kosmetik dan Barang Keperluan Rumah Tangga yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2020) - REYNOVA, SHALSABILA QATHRUNADA (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2021)
Earnings management is the practice of falsifying profits by company managers to achieve the desired amount of profit with the aim of deceiving stakeholders in evaluating the company's performance and financial condition. Investors are more attracted to companies with profitable returns. This study aims to identify and analyze several factors that are indicated to have an influence on the level of earnings management carried out by the company, namely the variables of profitability, company size, and leverage. The profitability variable was measured using the Return on Assets (ROA) ratio. Firm size variable is measured using the Natural Logarithm (LN) of the company's total assets. The leverage variable is measured using the Debt to Total Asset Ratio (DAR) ratio.The population of this study are companies listed on the Indonesia Stock Exchange in 2015-2020. While the sample in this study amounted to 7 samples from companies sub-sector cosmetics and household goods that can be tested. Sample selection using purposive sampling method based on predetermined criteria. The data analysis method used in this study is multiple linear regression with the basis of testing on descriptive statistical tests, classical assumption tests, and hypothesis testing. Based on the test results, it is known that the profitability variable has a significant positive effect on earnings management, the firm size variable has no significant effect on earnings management, and the leverage variable has a significant negative effect on earnings management.Keywords: Earnings Management, Profitability, Firm Size, Leverage.